The effect of different type of exercises on the isokinetic strength of quadriceps and hamstring muscles - Alpaslan Gorucu; Bekir Tokay (Türk Spor ve Egzersiz Dergisi)
This study was conducted with the aim of investigating the effect of three different types of exercise on the isokinetic strength of quadriceps and hamstring muscles. Thirty recreational athletes aged of 23.19 years on average participated in the study. In the study, the subjects were divided into 3 groups consisting of 10 individuals (bicycle group, plyometric group, and weight group). The athletes were given 3 different exercises for 3 days and 30 minutes per week for 6 weeks. Muscular strength and endurance as was measured at a constant angular velocity of 60º/s and 180º/s and concentric quadriceps and concentric hamstring strength test were measured before and after exercises by an isokinetic dynamometer (Cybex Humac Norm-2009). The Kruskal-Wallis H test was used to determine the differences among the groups in the study, and the Mann-Whitney U test was used to determine the group that is the source of these the differences. Wilcoxon test was conducted to determine pre - test post - test differences within the groups. As a result; Weight exercises during 6 weeks provided a significant increase in parameters at NDQPT60º/s, NDQAP60º/s and NDHPT60º/s in constant angular velocity values compared to cycling exercise in the same period. In terms of other parameters, exercises done in the same time period in all three groups did not show the same significant effect on strength development.